Advances in nanostructured thin film materials for solar cell applications - Ali, N. (2016)
This paper reviews recent advances in photovoltaic devices based on nanostructured materials and film designs, focusing on cadmium telluride (CdTe), copper zinc tin sulfide (CZTS), dye-sensitized solar cells (DSSCs) and perovskite solar cells. The current major challenges associated with the development of thin film solar cells are the reduction in manufacturing cost and increase in efficiency and performance. The CdTe and CZTS films have been investigated extensively due to its cheap and abundant elemental constituents and better physical properties. Solar cells based on the nanostructured technology including the DSSCs have also made wide impact into the solar cell industry in terms of manufacturing cost and improved efficiency. Perovskite solar cells have received significant interest recently due to its potential high efficiency.